Objective Pupillary Correlates of Photosensitivity in the Normal and Mild Traumatic Brain Injury Populations. - Truong, James Q.; Ciuffreda, Kenneth J. (Military Medicine, 2016)
Objective: No objective vision biomarker for photosensitivity currently exists. The present study sought to uncover potential biomarkers for photosensitivity within the pupillary light reflex.Methods: The pupillary light reflex was evaluated in those with mild traumatic brain injury (mTBI) and in normal individuals, with and without photosensitivity, under a range of test conditions. The Neuroptics DP-2000, infrared, binocular pupillometer was used for both binocular stimulation and recording. Twelve pupil parameters and 6 stimulus conditions were quantitatively assessed in 32 adults with mTBI and compared to 40 normal adult controls.Results: Normal subjects with photosensitivity exhibited four significant differences (p < 0.05) as compared with their nonphotosensitive cohort: larger constriction amplitude, faster average constriction velocity, faster peak constriction velocity, and slower recovery time. mTBI subjects with photosensitivity manifested six significant differences (p < 0.05) as compared with their nonphotosensitive cohort: larger baseline diameter, larger minimum diameter, faster peak dilation velocity, faster T50 and T75 recovery times, and a larger pupil diameter at 6 seconds poststimulus.Discussion: Several pupillometry parameters were significantly different in those with and without photosensitivity in both populations tested. These specific parameters could serve as potential, objectively based biomarkers for photosensitivity in these specific populations.